Stages of thought : the co-evolution of religious thought and science - Barnes, Michael Horace (Oxford University Press, 2000)
In Stages of Thought, Michael Barnes examines a pattern of cognitive development that has evolved over thousands of years--a pattern manifest in both science and religion. He describes how the major world cultures built upon our natural human language skills to add literacy, logic, and, now, a highly critical self-awareness. In tracing the histories of both scientific and religious thought, Barnes shows why we think the way that we do today. Although religious and scientific modes of thought are often portrayed as contradictory-one is highly rational while the other appeals to tradition and fa.